Leptospira interrogans infection in tegu lizard (Tupinambis merianae), Brazil - Fernandes, Juciê Jales; Pinheiro, Tiago Junior; Costa, Diego Figueiredo; Araújo Júnior, João Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Silva, Maria Luana Cristiny Rodrigues; Azevedo, Sérgio Santos; Alves, Clebert José; Higino, Severino Silvano Dos Santos (FapUNIFESP (SciELO), 2020)
We used 12 tegu lizards (Tupinambis merianae) from northeastern Brazil, and we reported nine (75%) Leptospira sp. PCR-positive animals and six (50%) seropositive. Leptospira sp. DNA sequencing revealed 99% similarity with L. interrogans. Our findings indicated that this species may play a role in the transmission of human leptospirosis.
Infecção por leptospira interrogans em lagarto teiú (Tupinambis merianae), Brasil
Keywords: Leptospirosis; Reptiles; Semiarid; Wild hosts